VITAMIN D STATUS:A LINK BETWEEN BLOOD GLUCOSE AND RENAL FUNCTION INDICATORS - RESHMA K; SUDHA K; AFZAL AHMAD (International Journal of Pharma and Bio Sciences, 2016)
Hypovitaminosis D is a widespread disorder targeting the current population across the world in general and developing countries in particular.Although UV radiation from sunlight is abundant in the tropical countries,malnutrition and skin pigmentation may be the principal cause for vitamin insufficiency in these regions.In addition to causing bone degeneration,vitamin D insufficiency is implicated in metabolic diseases like dyslipidemia,diabetes mellitus,endocrine dysfuntion like thyroid disorders and organ damage like liver and kidney disorders.One of the most common complications of diabetes mellitus is renal damage. This study focusses on the correlation of serum vitamin D levels with renal function in subjects with normal and elevated fasting blood glucose.Study group of 75 patients were categorized as Group1:Vitamin D sufficient(>30ng/ml); Group2:Vitamin D insufficient(20-30ng/ml) and Group3: Vitamin D deficient (<20ng/ml). Fasting glucose, serum creatinine and eGFR were estimated in serum of these subjects. Results indicated that elevated glucose was predominantly seen in Groups 2 & 3.A significant negative correlation of vitaminD levels with blood glucose in Groups 2&3 was observed which was more prominent in group3. A significant negative correlation between vitaminD and serum creatinine levels and a positive correlation between vitaminD and eGFRwere also observed in group 3.However age of the population did not appear to be a significant factor in this correlation study.Therefore this study establishes the fact that chronic complications of diabetes mellitus,particularly,renal damage may be aggravated with decreasing vitamin D levels.